The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12082390
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Is Positively Associated with Muscle Mass and Strength, but Not with Functional Capacity, in Kidney Transplant Patients

Abstract: Background: Our aim was to associate serum uric acid (UA) with muscle mass, strength and functional capacity in kidney transplant patients (KTPs). Methods: A cross-sectional study was performed on 113 KTPs. The fat-free mass and total and appendicular muscle mass were estimated by performing a bioelectrical impedance analysis. The strength was evaluated using the handgrip strength test (HGS) and the five times sit to stand test (5STS). The functional capacity was evaluated using the 4 m walk test and the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…In vivo, it may offer a neuroprotective advantage in the neurodegenerative Alzheimer’s disease [ 18 ], schizophrenia [ 19 ], Parkinson’s disease [ 20 ], multiple sclerosis [ 21 ], and serves as a depression biomarker [ 22 ]. SUA concentrations are linked to muscle strength and lean mass [ 23 ], although this was not shown in gastrointestinal tract cancer patients [ 24 ]. SUA may serve as a risk factor to predict poor thyroid function [ 25 ] or an indicator of malnutrition [ 15 ].…”
Section: Uric Acid and Goutmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, it may offer a neuroprotective advantage in the neurodegenerative Alzheimer’s disease [ 18 ], schizophrenia [ 19 ], Parkinson’s disease [ 20 ], multiple sclerosis [ 21 ], and serves as a depression biomarker [ 22 ]. SUA concentrations are linked to muscle strength and lean mass [ 23 ], although this was not shown in gastrointestinal tract cancer patients [ 24 ]. SUA may serve as a risk factor to predict poor thyroid function [ 25 ] or an indicator of malnutrition [ 15 ].…”
Section: Uric Acid and Goutmentioning
confidence: 99%
“…Allopurinol, a ULT medicine, has not shown any efficacy in the prevention of a first gout flare in patients with asymptomatic hyperuricemia [ 84 ]. Fundamentally, SUA level is associated with physical capacity and muscle strength in healthy subjects [ 23 , 24 ] and may only be a biological marker of non-gout conditions such as cardiovascular damage but is not a risk factor for its development [ 51 ]. Controversially, pseudo-gout, which is caused by calcium pyrophosphate deposition (CPPD), could have the same inflammatory symptoms as gout without hyperuricemia [ 85 ].…”
Section: The Causes Of Hyperuricemia Irrelevant To Goutmentioning
confidence: 99%
“…In addition to these risk factors, age-related decreases in hormone concentrations could cause loss of muscle mass and strength, such as growth hormone, testosterone, thyroid hormone, vitamin D, albumin and insulin-like growth factor 4 . Another metabolic factor, uric acid (UA), was studied most recently in the relationship with skeletal muscle mass and/or strength, but the conclusions were varied and ambiguous 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that UA was positively associated with muscle mass and strength in kidney transplant patients 6 . Besides, another cross-sectional study showed that a speci c range of serum UA levels may be associated with better hand grip strength among Chinese adults aged over 45 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Uric acid was also a major focus in this issue. Floriano and coworkers used bioelectrical impedance analysis, hand grip strength tests and five repetitions of sit-to-stand tests in a cohort of 113 kidney transplant recipients and showed that uric acid (UA) levels were positively associated with muscle mass and strength, but not with functional capacity [ 11 ], while Dominguez-Zabrano et al underlined the antioxidant properties of uric acid in HD patients [ 12 ]. In another interesting study involving living kidney donors, Oba and coworkers showed that single nephron Glomerular Filtration Rate (GFR) was directly associated with protein intake but not with sodium intake, BMI or arterial pressure [ 13 ].…”
mentioning
confidence: 99%